Clay Mineralogical Records in the North Bohai Coast of China in the Last Century: Sediment Provenance and Morphological Implications - Sun, Shuang; Li, Yan; Liu, Dawei; Hu, Ke (Frontiers in Earth Science, 2022)
Provenance identification of the clastic sediments is critical for paleoenvironmental and morphological reconstruction on the estuarine coast. The North Bohai Coast (NBC) receives tremendous sediments mainly from the Liaohe and Daling fluvial systems. However, the detailed morphological evolution is still unclear due to the lack of precise discrimination of the sediment provenance. In this study, the clay mineralogy of the coastal sediments in the NBC was investigated to determine variation of the fine-grained sediment sources in the last century. The clay mineral content in the modern riverine sediments in the NBC was used to model sedimentary contribution from different fluvial systems. 210Pb and 137Cs radioactivity was measured to constrain the timing of centennial marine–terrestrial sedimentation. The migration of coastline and river channels in the NBC during the last hundred years was reconstructed by digitalizing the historical charts and satellite image. 210Pb following the CIC model and 137Cs dating are considered not applicable for the dated cores, whilst 210Pb using the CRS model yields acceptable chronologic results. Non-linear modeling results of the clay mineral composition are consistent with the lithological and coastal geomorphologic constraints. The outcome of provenance discrimination indicates that clay minerals in western and eastern NBC are mainly derived from the Daling and Liaohe rivers, respectively. In the middle NBC, the Daling River input was relatively major during the 1910s, 1940s, 1980s, and 2000s. The increase of Daling River input in the first two periods resulted from progradation and river channel migration, respectively. The fluvial contribution from the Liaohe River was major in the middle NBC during 1920–1940 and 1950–1970 AD, which attributes to rapid progradation of the Liaohe River and channel migration of the Daling River, respectively.